2017
DOI: 10.1016/j.ijso.2017.09.003
|View full text |Cite
|
Sign up to set email alerts
|

The 2016 revised ACR criteria for diagnosis of giant cell arteritis – Our case series: Can this avoid unnecessary temporal artery biopsies?

Abstract: Background Temporal artery biopsy (TAB) is considered the gold standard for diagnosing Giant Cell Arteritis (GCA). The aim of this study was to compare the functional utility of the 2016 revised ACR (rACR) criteria against the original ACR criteria with a view to avoiding TABs in select groups. We also aimed to investigate the temporal relationship of positive biopsies. Methods A retrospective study was conducted of patients undergoing TAB from August 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 14 publications
0
38
0
4
Order By: Relevance
“…Sait et al compared the functional utility of rACR criteria against the original ACR criteria and found that the more extensive rACR can serve as a more useful guide to reduce the number of unnecessary biopsies. [16] In case of TAB-positive results in the first and second five years, the odds ratio was approximately 2.7 (comparing second five years to the first five years), even though the P-value was borderline. The increase in the specimen length can be due to human factors.…”
Section: Main Finding and Conclusionmentioning
confidence: 96%
See 1 more Smart Citation
“…Sait et al compared the functional utility of rACR criteria against the original ACR criteria and found that the more extensive rACR can serve as a more useful guide to reduce the number of unnecessary biopsies. [16] In case of TAB-positive results in the first and second five years, the odds ratio was approximately 2.7 (comparing second five years to the first five years), even though the P-value was borderline. The increase in the specimen length can be due to human factors.…”
Section: Main Finding and Conclusionmentioning
confidence: 96%
“…Based on the 2016 rACR criteria for the diagnosis of GCA, Sait et al proposed a simple management plan: (1) 2016 rACR scores ≤ 2 may not mandate a biopsy as these patients are very unlikely to have GCA; (2) patients with scores ≥ 5 will also not need TAB as they are likely to have GCA and should continue steroid therapy; and (3) a biopsy will be required in cases with scores of 3 and 4 because these patients have the most variability in TAB results. [16] However, further studies involving multiple centers with firm inclusion criteria should be performed before an algorithm that avoids biopsy in GCA management is applied. In our study, TAB-positive patients had a higher mean overall rACR score than the TAB-negative patients.…”
Section: Main Finding and Conclusionmentioning
confidence: 99%
“…According to some studies and to 2016 revised ACR criteria, which proposed a clinical management tool using rACR scores, the temporal artery biopsy is not necessary if rACR ≥ 5 (7,8). In our case, we have a rACR score of 8 points, so this 71-year-old woman has a certain diagnosis of Horton's disease (9,10).…”
Section: Discussionmentioning
confidence: 73%
“…The demographic characteristics by diagnosis were consistent with known characteristic distributions for these types of vasculitis. For example, the ratios between female and male participants in this study were characteristic of each disease (25)(26)(27).…”
Section: Study Populationmentioning
confidence: 90%